Power Electronic Two-phase Orthogonal System with HF Input and - Dobrucký, B.; Špánik, P.; Kabašta, M. (Elektronika ir Elektrotechnika, 2009)
The paper deals with the direct single- to two-phase conversion system as a new version of classical indirect single- to three-phase conversion system with DC link. It’s supposed that such a system will supply two-phase synchronous or induction motors. The proposed drive in comparison with currently used conventional drives reduces the number of power switching elements of the converter, also heavy and bulky DC link, which increases the drive’s dependability and reliability, and brings lower investment in power electronics used in drive. The system can be used in high power traction application as well as in lower power aircraft application using HF traction transformer or HF generator, respectively. Ill. 12, bibl. 27 (in English; summaries in English, Russian and Lithuanian).